Perceived Labor Productivity in Small Firms—The Effects of High–Performance Work Systems and Group Culture through Employee Retention - Patel, Pankaj C.; Conklin, Betty (Entrepreneurship Theory and Practice, 2012)
In small firms, high–performance work systems (HPWS) may not always yield benefits that outweigh their costs. Using a sample of 145 small enterprises (SEs) with 10–100 employees, we examine how small firms may realize mutually reinforcing effects of group culture on HPWS to increase employee retention and improve perceived labor productivity. Using a novel methodology, we find that employee retention does not mediate the effects of HPWS on perceived labor productivity, but that mediation becomes significant and increases with greater levels of group culture. This study provides insights into conditions in which HPWS can enhance SE perceived labor productivity.